Imam Al-Kazem, peace be upon him, and his role in the reform and education of the nation Brief analytical view (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon the most honorable of all creatures, and upon his familymyamine. To follow the reform and educational approach of the Prophet, may God bless him and his family, in the nation, the researcher is required toTo spend a large part of his life trying to be aware of those bright aspects in the life of the nation.